Analisis Efektivitas Pembelajaran Tematik melalui Daring di Kelas IV SD Inpres 6/86 Biru - Dhea Amanda Febriani; Abd Hafid; Sudirman Sudirman (JPPSD: Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2021)
The problem in this study is that educators only give assignments to students without giving explanations first, educators do not use technology to convey learning so that students find it difficult to understand the learning delivered.This research is a qualitative descriptive research. Aims to describe a picture of the effectiveness of thematic learning through online. The results showed that it was difficult for educators to integrate several subjects into one theme, educators did not use interesting and appropriate learning methods/media in learning, educators did not provide direct and meaningful experiences for students, students were not able to fully understand learning. The conclusion of the study is that thematic learning through online is not effective in learning.